Investigating the Mediating Role of Perceived Organizational Support in the Relationship Between Sense of Coherence, Professional Ethics, and Job Performance of Nurses - Narges Rasouli; Alireza Heidari; Farah Naderi; Fatemeh Sadat Marashian (Journal of Client-centered Nursing Care, 2020)
Background: Job performance is one of the basic concepts in organizations, based on which, the responsibilities and success of each individual in the organization are realized. The main objective of the current study was to investigate the mediating role of perceived organizational support in the relationship between Sense of Coherence (SOC), professional ethics, and the job performance of nurses in Ahvaz City, Iran. Methods: This study was model-based testing research. The statistical population included all the nurses working in Golestan Hospital of Ahvaz City, Iran, in 2019. Of them, 252 nurses were selected as the study sample using the voluntary sampling method. The research instruments included Paterson’s job performance questionnaire, the SOC scale, professional ethics questionnaire, and survey of perceived organizational support. Model fit was evaluated using path analysis with AMOS software. Results: The results showed that all direct paths, except for the path from the SOC to job performance were significant (P<0.01). Moreover, the indirect paths through perceived organizational support to job performance were also significant (P<0.01). Conclusion: According to the study results, the proposed model had a good fit, and it can be considered as an important step towards identifying the factors affecting the job performance of nurses.